De l’occidentalisation du soufisme à la réislamisation du New Age ? Sufi Order International et la globalisation du religieux - Alix Philippon (Revue des Mondes Musulmans et de la Méditerranée)
Sufi Order International (SOI) was founded in the West and for a Western clientele at the beginning of the XXth century by Hazrat Inayat Khan, a musician and a disciple of the Indian Sufi Order of the Chishtiyya. This group gives the example of a Western Sufism that has found its place in the New Age galaxy by embracing syncretistic forms of spirituality and by emphasizing the universalism of the Sufi message, beyond Islam per se. Conversely, this Western Sufism has started to fertilize the Muslim lands by fulfilling the demands of a liberal and Westernized bourgeoisie, generally opposed to the religious offers available at home and that has found in this universalist Sufi discourse an acceptable way to Islam, transformed by religious modernity. On the basis of fieldworks in Switzerland and Pakistan within SOI circles, this article aims at analyzing jointly the dynamics of the mode of contemporary belief and those of religious globalization.